Children's concepts of gears and their promotion through play. Issue 1 (3rd July 2020) - Reuter, Timo; Leuchter, Miriam
Abstract: The mechanical transmission of motion, which is observable in gears' turning direction (TD) and turning speed (TS) can be understood as part of the core concept "force and motion". Previous studies have suggested that most children before the age of nine have naïve concepts of gears' TD and TS. However, these studies relied on children's explanation data and might have therefore underestimated young children's potential. Moreover, these studies did not examine whether preschoolers can overcome their naïve concepts through teaching. Recently, educators have proposed guided play as an educational approach that combines children's play with teacher guidance in a purposefully designed environment. We conducted two subsequent studies. In Study 1, we investigated the children's (naïve) concepts of gears' TD and TS with a cross‐sectional approach using a nonverbal test procedure. This study comprised 248 children aged 5–10 years and 73 adults. The results showed that the proportion of children with adequate concepts increased with age. More specifically, 7‐ to 8‐year‐olds differed significantly from 5‐ to 6‐year‐olds, indicating a developmental shift around this age. However, naïve concepts of TS were more persistent with age than naïve concepts of TD. Altogether, the results indicated the potential to foster 5‐ to 6‐year‐olds' concepts of both TD and TS in an intervention. Thus, in Study 2, we developed and tested a guided play intervention to foster 5‐ to 6‐year‐old children's concepts of TD and TS. We conducted a prepost‐intervention design with a guided play group ( n = 19) and a free play group ( n = 21). The results suggested stronger learning gains in the guided play group ( d TD = 0.337, d TS = 0.758) than in the free play group ( d TD = 0.224, d TS = 0.158).